2021
DOI: 10.3390/jpm11070615
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Marijuana on Antidepressant Treatment in Adolescents: Clinical and Pharmacologic Considerations

Abstract: The neuropharmacology of marijuana, including its effects on selective serotonin reuptake inhibitor (SSRI)/antidepressant metabolism and the subsequent response and tolerability in youth, has received limited attention. We sought to (1) review clinically relevant pharmacokinetic (PK) and pharmacodynamic (PD) interactions between cannabinoids and selected SSRIs, (2) use PK models to examine the impact of cannabinoids on SSRI exposure (area under curve (AUC)) and maximum concentration (CMAX) in adolescents, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 63 publications
0
14
0
1
Order By: Relevance
“…This would increase plasma STR concentration and serotonin concentrations, reducing tolerability secondary to activation. Thus, the combined use of CBD plus STR appears to increase the risk of concentration-related SSRI side effects ( Jakubovski et al, 2016 ; Vaughn et al, 2021 ). A recent case report showed a pharmacokinetic interaction between CBD and STR in a patient treated with STR for depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This would increase plasma STR concentration and serotonin concentrations, reducing tolerability secondary to activation. Thus, the combined use of CBD plus STR appears to increase the risk of concentration-related SSRI side effects ( Jakubovski et al, 2016 ; Vaughn et al, 2021 ). A recent case report showed a pharmacokinetic interaction between CBD and STR in a patient treated with STR for depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study of es/citalopram‐treated adolescents/young adults aged 17–24 years, CBD significantly increased citalopram plasma concentration 27 , and in pharmacokinetic models of adolescents treated with sertraline or escitalopram, CBD and THC increase sertraline and es/citalopram C MAX and AUC 0‐24 . Finally, it is noteworthy that a recent examination of the Food and Drug Administration Adverse Event Reporting System database revealed that co‐administration of CBD and CYP2C19‐metabolized SSRIs increased the risk of some SSRI‐related side effects (e.g., diarrhea, dizziness, and fatigue), which may relate to SSRI concentrations 28 …”
Section: Ssri‐related Adverse Effects In Children and Adolescentsmentioning
confidence: 99%
“…To our knowledge, only one study has examined this possible interaction of marijuana and AD use among adolescents [ 182 ]. Nevertheless, this matter warrants intensive research before a definitive conclusion can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has not been explored fully; yet, a few similarities between these compounds’ mechanisms of action can point to a competitive effect. Although there are limited studies of direct SSRI–cannabinoid interactions, accumulating data suggest the potential for interactions [ 182 ].…”
Section: Antidepressant Treatment Combined With Cannabis Use: a Gap In Knowledgementioning
confidence: 99%